Sea Cucumber Fishery and Trade in Sta. Cruz, Davao Del Sur, Philippines: Supply Chains and Cost-Benefit Analyses - Shuck, Vlademir A; Mondoyo, Rod Norbert D; Acuňa , Thaddeus R; Gamboa, Ruth U (Asian Journal of Agriculture and Rural Development, 2013)
In the country, sea cucumbers are exploited almost exclusively for export. It is harvested in three ways; commercial fishing, artisanal fishing and gleaning. These methods provide disproportionate economic benefits to these players in the supply chain. In this study, sea ranching, a new culture system for sea cucumber was analyzed in terms of its economic and commercial viability. Under the sea ranching system Holothuria scabra (sandfish) is the species being raised mainly due to its high economic value. Under the traditional method, labor comprises the largest share in the total cost, while the cost of juvenile and labor (monitoring cost) accounts to almost 87% in the sea ranching system. Based on the results of the study, selling dried sandfish would gain positive net profit, while selling wet sandfish will incur a net loss. A significant difference in income was also observed between fishers who rely on traditional method and those who will adopt the new system. Sea ranching system is a very promising method that is expected to be beneficial both to the community and the environment. However, high capital requirement, uninformed community and the lack of support from the government and concerned agencies remains to be a big challenge.